Children's constructions of gender: A participatory project - Mohana, Malini (Department of Psychology, 2020)
Studies on the construction of gender have largely focussed on adolescents and young adults in South Africa. This leaves a significant gap in understanding the ways in which gender is constructed and negotiated by younger children. This study, therefore, investigated how younger children narrate and experience their gendered lives, and whether these stories resisted or maintained dominant narratives of gender. Twelve participants between the ages of eight and fourteen participated. The research used participatory action research (PAR) methods. Specifically, Photovoice, journaling, collages and drawing were used to represent the stories and narratives that the participants chose to share. The Photovoice component culminated in a community exhibition which showcased the participants’ photos. In addition, the participants took part in focus groups and individual interviews. The focus group transcripts, individual interview transcripts, collages, photographs, drawings and journal entries were analysed using thematic narrative analysis. The study showed that children construct gender based on contradictory messaging, and exercise defiance of normative gendered constructs within the limits of heteronormative gender identity. Four main narrative themes emerged: Negotiating gendered expression; Normalisation of gendered violence; Subjugating female bodies; Narratives of conformity and resistance. Based on the findings, the recommendation was made to use play as both a means of exploration and education in children’s understanding of gender.